2009
DOI: 10.1007/s11606-009-0925-9
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Biopsy-Negative Giant Cell Arteritis Presenting as Fever of Unknown Origin

Abstract: Fever of unknown origin (FUO) presents a diagnostic challenge. Giant cell arteritis (GCA) may present with FUO and this entity should be included in the differential of elderly patients who present with constitutional symptoms. While a temporal artery biopsy is considered the gold standard for the diagnosis of GCA, a subset of patients with large vessel involvement by GCA may have a negative temporal artery biopsy and no cranial symptoms. We present a 79 year-old woman with FUO and negative temporal artery bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In suspected temporal arteritis, the diagnostic role of FDG PET/CT is limited and is recommended that temporal artery biopsy performed prior to further evaluation of the FUO by PET/CT . However, FDG PET/CT may demonstrate inflammatory changes in larger arteries sized >4 mm during various other inflammatory processes of blood vessels .…”
Section: Methodsmentioning
confidence: 99%
“…In suspected temporal arteritis, the diagnostic role of FDG PET/CT is limited and is recommended that temporal artery biopsy performed prior to further evaluation of the FUO by PET/CT . However, FDG PET/CT may demonstrate inflammatory changes in larger arteries sized >4 mm during various other inflammatory processes of blood vessels .…”
Section: Methodsmentioning
confidence: 99%
“…This has been reinforced by numerous case reports describing the use of 18F-FDG PET scanning to diagnose GCA. [63][64][65] PET scanning, in comparison to MRI, has shown comparable sensitivities in diagnosing. However, PET scanning allows simultaneous identification of more affected vessels than MRI.…”
Section: Use Of Combined Pet-ct In Lvvmentioning
confidence: 99%
“…In three patients with vasculitis, Otsuka et al using PET/CT scan demonstrated an increase of FDG-uptake along the aorta and carotid artery; after steroid therapy a normalization of FDG-uptake in the respective vessels was observed [3]. FDG scan detects the early stage of GCA, and identifies the extent of the sites of inflammation of medium and large vessels [4][5][6]. In patients with fever of unknown origin, FDG scan can also show signs of vasculitis [7].…”
mentioning
confidence: 99%